Crashworthiness Performance of Circular Hybrid Crash Box with Friction Model Due to Axial Load - Wakhidah, Delia Hani; Choiron, Moch Agus; Purnowidodo, Anindito; Irawan, Yudy Surya (International Journal of Integrated Engineering, 2024)
In the previous study, hybrid crash box combines low-density and high-strength of composite materials with aluminium materials had been developed. In this study, circular hybrid crash box with friction model is investigated. Crash box design is modelled by using computer simulation with ANSYS Workbench. Composite Carbon Toray T300 – Epoxy Resin (CCE) and metal Aluminium Alloy 6063 (AA6063) is used as hybrid crash box material. Axial loading with a speed of 10 m/s is applied to circular hybrid crash box model by using impactor with mass of 100 kg. The orientation angle of composite lay-up and hybrid material configuration with two models of friction was running as 16 models. Energy absorption and deformation pattern were observed to determine crashworthiness performance. Based on the results, it can be denoted that the Al-Ko45 with friction model of 0,68 shows largest energy absorption of 7,53 kJ with specific energy absorption of 32,552 kJ/kg. The deformation pattern produces mixed mode with progressive crushing folding that can enhance energy absorption